Legal Footprints / Legal Footprints in Redfern: A photoessay of Carol Ruff’s ‘40,000 Years’ Mural in Lawson Street, Redfern, Sydney, Australia - Olivia Barr (Law Text Culture, 2017)
Through an exploration in poetry, essay and photographs, I ask and interrogate the jurisprudential question: What are our legal footprints? As a global activity, walking is everywhere, yet it is important to notice the location of where we walk if we are to notice how we walk legally. Addressing the global through the local, because we all walk somewhere, this autoethnographic essay unfolds across a triptych of genres as a way of eliciting some fractal patterns in the movements of laws, the laws of movement, and the place of our feet, legally, in this maze of non-linear movements. More specifically, I argue location matters for how we notice, experience and understand the active nature of laws’ moving places in the world, and how this relates to walking. How, then, might we understand the ramifications of our global footprints? In a common law world, where common law attaches to subjects through the body, of more specifically, the feet, the nature of our legal footprints especially matter. In Australia, for example, what happens when we walk with multiple forms of laws: one carried by feet, and one carried by land? This is a challenge raised by the question of legal footprints, and contemplated in this experimental essay through a method of a minor jurisprudence.